2005
DOI: 10.3748/wjg.v11.i42.6656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytokine gene polymorphism on histological activity index, viral load and response to treatment in patients with chronic hepatitis C genotype 3

Abstract: There is no significant correlation between cytokine polymorphisms and HAI except for the polymorphisms of anti-inflammatory cytokine IL-10, which may influence hepatic inflammatory activity and fibrosis in patients with chronic hepatitis C genotype 3. Sustained virological response in this genotype does not seem to be influenced by cytokine gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 48 publications
8
47
1
2
Order By: Relevance
“…In accordance with our findings, some significant associations with regard to IL-18 and IFN-c polymorphisms have been observed [30,35]. However, other studies revealed opposing results [36,37]. These contradictory results could be partly explained by the extreme complexity in the cytokine network related to the intricate interactions of cytokines by which they induce or suppress their own synthesis or that of other cytokines, and antagonize or synergize with each other in many different and often redundant ways.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In accordance with our findings, some significant associations with regard to IL-18 and IFN-c polymorphisms have been observed [30,35]. However, other studies revealed opposing results [36,37]. These contradictory results could be partly explained by the extreme complexity in the cytokine network related to the intricate interactions of cytokines by which they induce or suppress their own synthesis or that of other cytokines, and antagonize or synergize with each other in many different and often redundant ways.…”
Section: Introductionsupporting
confidence: 53%
“…In line with our finding, a large scale study conducted by Dai et al [35] on Taiwanese HCVinfected patients described a significant increase of IFN-c ?874T allele in cirrhotic patients. Nevertheless, other studies failed to demonstrate any association between T allele and hepatitis C severity [36,37]. In reality, in multifactorial diseases like HCV infection, where the host, the pathogen and the environmental factors all contribute to disease outcome, genetic association studies focused on a single polymorphism are often weak and non-informative.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of IL-10 gene polymorphisms indicated a variation between the proinflammatory and anti-inflammatory cytokine responses, which may have resulted in immunodeficiency to HCV infection in Pakistan [21]. Meanwhile, no significant correlation has been found between SNPs of IL-10 and histological activity index in HCV patients [22]. Accordingly, in the current study, we further investigated the possible SNPs in IL-10 and IL-4 that may occur in samples collected from Egyptian patients.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the genotype distributions of TNF-α gene (−238 and −308) in the Chinese HD patients were similar to those in the general Chinese population, 15 but that the frequencies of A alleles and AA genotypes of TNF-α gene (−238 and −308) were lower than those in Pakistan and Ireland population. 30,31 Furthermore, in this study, no link was identified between the two SNPs of TNF-α promoter gene and susceptibility to HCV infection or the viral persistent infection in Chinese HD patients. The discrepancy above could be contributed to the special HD population in our study, who were different from the general population, since HD patients infected with HCV will be under the triple influence of uremia, the HD procedure, and the HCV infection itself.…”
Section: Discussionmentioning
confidence: 86%